The Pagoda of the Gods: A case for Indigenous Karen sacred sites as Special Cultural Zones along Thailand’s borders - Phatthanaphraiwan, Suwichan; Zeitler, Lilly; Fairfield, Benjamin (Forest and Society, 2022)
Burgeoning recognition of Indigenous traditional ecological knowledge and livelihood practices have led to ‘Special Cultural Zone’ designations for some traditionally Indigenous lands in Thailand. Simultaneously, the Thai government has designated 10 Special Economic Zones (SEZs) to bolster trade and investments along its borders without acknowledging the pre-existence of Indigenous peoples. SEZs intersect with sites of notable cultural significance, such as Kho Pho Lu (Pagoda of the Gods), a sacred site for Indigenous Karen near Mae Sot in Tak province. Detailed ethnographic and interview findings show the resilience of these sacred sites and embedded ritualistic place-making practices that persist despite a legacy of Indigenous displacement. Ethnobotanical findings of 39 sampled taxa in the sacred forest of Kho Pho Lu indicate that cultural and spiritual practices support local biodiversity conservation. Potential biocultural conservation approaches include the adoption of ‘Special Cultural Zones’ to promote Indigenous well-being and the preservation of biocultural diversity in Thailand.